Universities on Fire : Higher Education in the Climate Crisis - Alexander, Bryan, 1967- (Book collections on Project MUSE., 2023)
"Scientists agree that we are on the precipice of a global climate crisis. How will it transform colleges and universities? In 2019, intense fires in the San Francisco Bay Area closed universities and drove afflicted people to shelter at other campuses. At the same time, extraordinary fires ravaged eastern Australia. Several universities responded by promising material and research support to damaged businesses while also hosting refugees and emergency response teams in student residence halls. This was an echo of the devastation wreaked by Hurricane Katrina on Tulane University in 2005.In Universities on Fire, futurist Bryan Alexander explores higher education during an age of unfolding climate crisis. Powered by real-world examples and the latest research, Alexander assesses practical responses and strategies by surveying contemporary programs and academic climate research from around the world. He establishes a model of how academic institutions may respond and offers practical pathways forward for higher education. How will the two main purposes of education-teaching and research-change as the world heats up? Alexander positions colleges and universities in the broader social world, from town-gown relationships to connections between how campuses and civilization as a whole respond to this epochal threat.Current studies of climate change trace the likely implications across a range of domains, from agriculture to policy, urban design, technology, culture, and human psychology. However, few books have predicted or studied the effects of the climate crisis on colleges and universities. By connecting climate research to a deep, futures-informed analysis of academia, Universities on Fire explores how climate change will fundamentally reshape higher education"--